Om Jens Sinning og hans »Oratio« - Glebe-Møller, Jens (Kirkehistoriske Samlinger, 2000)
Jens Sinning, one of Melanchthon’s many Danish students, was professor at the University of Copenhagen from 1537 until his death 10 years later. His only remaining contribution to Danish theological literature is his »Oratio«. Sinning follows in the footsteps of his beloved master when he speaks of the importance of the study of philosophy for students of theology. Above all he underlines the necessity of philosophical studies for the understanding of the bible. The article presents Sinning and his »Oratio« in its proper academic setting.